Life Skills of Filipino Emerging Adults of a Catholic Higher Education Institution in Central Philippines - Loren Lloyd V. Pahilanga; Joel M. Bual; Dennis V. Madrigal (Indonesian Journal Of Educational Research and Review, 2023)
Life skills are essential among students in countering the circumstances of life. However, due to the shifting instructional modality, their skills acquisition was compromised. Thus, this study aims to analyze the life skills of Filipino emerging adults in terms of self-awareness, empathy, effective communication, interpersonal relations, creative thinking, critical thinking, decision-making, problem-solving, coping with emotions, and coping with stress. Likewise, it determined the relationship between the demographics and life skills. Lastly, it investigated what demographics predict their life skills. This study using a quantitative design, a standardized questionnaire was responded by 298 college students. In data analysis, mean and standard deviation were utilized in analyzing the students’ level of life skills. The result reveals that the life skill was rated average which signifies the need for improvement. The lowest areas were coping with stress, coping with emotions, effective communication, and interpersonal relationship. Meanwhile, their family income, family structure, and academic classification were found no correlation with life skills. However, the degree program was significantly related. Lastly, the degree program was found to be a life skill predictor. Hence, continuous improvement is critical in their life skill acquisition and the school plays a potential role in advancing this.